Diversity and functional group composition drive biogeographic patterns in marine biogenic structural complexity - Dean S. Janiak; Matthew A. Whalen; David R. Branson; Soledad Álvarez; Gail V. Ashton; Nicholas M. Bartkowiak; Simon J. Brandl; João Canning‐Clode; Jordan M. Casey; Max C. N. Castorani; Carolina César‐Ávila; Rachel Collin; et al. (Ecology, 2026)
Biogenic structural complexity is a key driver of biodiversity and ecosystem functioning, yet its ecological and environmental determinants remain poorly understood across broad biogeographic scales. Here, we conducted standardized 90‐day field experiments at 16 coastal sites, spanning a 41‐degree latitudinal gradient, using naturally assembled marine fouling communities on settlement panels. We measured rugosity as our metric of biogenic structural complexity and modeled its relationship with species richness, community composition, community growth rates, and abiotic conditions (salinity and temperature). Species richness increased with temperature and salinity and declined with latitude, with more diverse communities exhibiting greater biogenic complexity due to increased morphological variation. At high‐latitude sites, low‐diversity communities dominated by arborescent bryozoans also had increased complexity. Structural equation models showed that abiotic conditions influenced growth and composition, which in turn shaped complexity. Warmer, saltier sites promoted richness‐driven complexity, while colder conditions favored structurally important dominant taxa. We found that biodiversity is important not only as a beneficiary of complexity but also as a contributor to complexity itself within fouling communities. Our results also demonstrate that both species richness and functional group identity regulate biogenic complexity across environmental gradients, underscoring biodiversity's role in supporting ecosystem structure and resilience in the face of increasing global change. Understanding these relationships is essential for biodiversity conservation and the management of marine ecosystems facing increasing anthropogenic pressures.

Recreational boats routinely transfer organisms and promote marine bioinvasions - Gail V. Ashton; Chela J. Zabin; Ian C. Davidson; Gregory M. Ruiz (Biological Invasions, 2022)

A global analysis of complexity–biodiversity relationships on marine artificial structures - Elisabeth M. A. Strain; Peter D. Steinberg; Maria Vozzo; Emma L. Johnston; Marco Abbiati; Moises A. Aguilera; Laura Airoldi; J. David Aguirre; Gail Ashton; Maritina Bernardi; Paul Brooks; Benny K. K. Chan; et al. (Global Ecology and Biogeography, 2021)
Aim Topographic complexity is widely accepted as a key driver of biodiversity, but at the patch‐scale, complexity–biodiversity relationships may vary spatially and temporally according to the environmental stressors complexity mitigates, and the species richness and identity of potential colonists. Using a manipulative experiment, we assessed spatial variation in patch‐scale effects of complexity on intertidal biodiversity. Location 27 sites within 14 estuaries/bays distributed globally. Time period 2015–2017. Major taxa studied Functional groups of algae, sessile and mobile invertebrates. Methods Concrete tiles of differing complexity (flat; 2.5‐cm or 5‐cm complex) were affixed at low–high intertidal elevation on coastal defence structures, and the richness and abundance of the colonizing taxa were quantified after 12 months. Results The patch‐scale effects of complexity varied spatially and among functional groups. Complexity had neutral to positive effects on total, invertebrate and algal taxa richness, and invertebrate abundances. However, effects on the abundance of algae ranged from positive to negative, depending on location and functional group. The tidal elevation at which tiles were placed accounted for some variation. The total and invertebrate richness were greater at low or mid than at high intertidal elevations. Latitude was also an important source of spatial variation, with the effects of complexity on total richness and mobile mollusc abundance greatest at lower latitudes, whilst the cover of sessile invertebrates and sessile molluscs responded most strongly to complexity at higher latitudes. Conclusions After 12 months, patch‐scale relationships between biodiversity and habitat complexity were not universally positive. Instead, the relationship varied among functional groups and according to local abiotic and biotic conditions. This result challenges the assumption that effects of complexity on biodiversity are universally positive. The variable effect of complexity has ramifications for community and applied ecology, including eco‐engineering and restoration that seek to bolster biodiversity through the addition of complexity.

An experimental test of stationary lay-up periods and simulated transit on biofouling accumulation and transfer on ships - Ian C. Davidson; George Smith; Gail V. Ashton; Gregory M. Ruiz; Christopher Scianni (Biofouling, 2020)

Fatty acid composition as a dietary indicator of the invasive caprellid, Caprella mutica (Crustacea: Amphipoda) - Elizabeth J. Cook; Richard Shucksmith; Heather Orr; Gail V. Ashton; Jørgen Berge (Marine Biology, 2010)

Mitochondrial DNA reveals multiple Northern Hemisphere introductions of Caprella mutica (Crustacea, Amphipoda) - GAIL V. ASHTON; MARK I. STEVENS; MARK C. HART; DAVID H. GREEN; MICHAEL T. BURROWS; ELIZABETH J. COOK; KATE J. WILLIS (Molecular Ecology, 2008)
Caprella mutica (Crustacea, Amphipoda) has been widely introduced to non‐native regions in the last 40 years. Its native habitat is sub‐boreal northeast Asia, but in the Northern Hemisphere, it is now found on both coasts of North America, and North Atlantic coastlines of Europe. Direct sequencing of mitochondrial DNA (cytochrome c oxidase subunit I gene) was used to compare genetic variation in native and non‐native populations of C. mutica . These data were used to investigate the invasion history of C. mutica and to test potential source populations in Japan. High diversity (31 haplotypes from 49 individuals), but no phylogeographical structure, was identified in four populations in the putative native range. In contrast, non‐native populations showed reduced genetic diversity (7 haplotypes from 249 individuals) and informative phylogeographical structure. Grouping of C. mutica populations into native, east Pacific, and Atlantic groups explained the most among‐region variation (59%). This indicates independent introduction pathways for C. mutica to the Pacific and Atlantic coasts of North America. Two dominant haplotypes were identified in eastern and western Atlantic coastal populations, indicating several dispersal routes within the Atlantic. The analysis indicated that several introductions from multiple sources were likely to be responsible for the observed global distribution of C. mutica , but the pathways were least well defined among the Atlantic populations. The four sampled populations of C. mutica in Japan could not be identified as the direct source of the non‐native populations examined in this study. The high diversity within the Japan populations indicates that the native range needs to be assessed at a far greater scale, both within and among populations, to accurately assess the source of the global spread of C. mutica .

Distribution of the introduced amphipod, Caprella mutica Schurin, 1935 (Amphipoda: Caprellida: Caprellidae) on the west coast of Scotland and a review of its global distribution - Gail V. Ashton; Kate J. Willis; Elizabeth J. Cook; Michael Burrows (Hydrobiologia, 2007)